Measuring changes in travel behavior patterns due to rainfall on urban roads - Suwanno, Piyapong; Yaibok, Chaiwat; Jitpat, Prasan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
Globally, climate change has caused increases in frequency, duration and rainfall intensity. High rainfall can cause flooding on roads that results in traffic jams, with travelers modifying their routes to avoid congestion. Collection of multiple data is necessary to understand travel behavior. Bluetooth is a short-range wireless technology that can quickly collect large amounts of data. Tracking sequences of Bluetooth-enabled devices including cell phones, headphones and in-car audio systems can be used to record the movement of vehicles within a network. Bluetooth tracking sequences may be incomplete or inconsistent due to data failure of the nodes and tracking devices. One solution is to cluster together similar Bluetooth tracking sequences. The deoxyribonucleic acid (DNA) alignment method was applied to identify similarity/distance distribution between Bluetooth tracking path group sequences. during rainy days, with results used to plan new routes